A central role for the acid sphingomyelinase/ceramide system in neurogenesis and major depression. (23rd May 2015) - Gulbins, Erich; Walter, Silke; Becker, Katrin Anne; Halmer, Ramona; Liu, Yang; Reichel, Martin; Edwards, Michael J.; Müller, Christian P.; Fassbender, Klaus; Kornhuber, Johannes
<x xml:space="preserve">Abstract</x> Major depressive disorder is a severe and chronic illness with high lifetime prevalence and high incidence of suicide. Major depression is caused in part by an imbalance between factors that positively and negatively control neurogenesis. Anti‐depressants inhibit the acid sphingomyelinase/ceramide system and thereby reduce the sum of negative factors restoring neurogenesis, neuronal survival, and improved mood.